A Current Update on the Role of HDL-Based Nanomedicine in Targeting Macrophages in Cardiovascular Disease - Alankrita Rani; Gunther Marsche (MDPI AG, 2023)
High-density lipoproteins (HDL) are complex endogenous nanoparticles involved in important functions such as reverse cholesterol transport and immunomodulatory activities, ensuring metabolic homeostasis and vascular health. The ability of HDL to interact with a plethora of immune cells and structural cells places it in the center of numerous disease pathophysiologies. However, inflammatory dysregulation can lead to pathogenic remodeling and post-translational modification of HDL, rendering HDL dysfunctional or even pro-inflammatory. Monocytes and macrophages play a critical role in mediating vascular inflammation, such as in coronary artery disease (CAD). The fact that HDL nanoparticles have potent anti-inflammatory effects on mononuclear phagocytes has opened new avenues for the development of nanotherapeutics to restore vascular integrity. HDL infusion therapies are being developed to improve the physiological functions of HDL and to quantitatively restore or increase the native HDL pool. The components and design of HDL-based nanoparticles have evolved significantly since their initial introduction with highly anticipated results in an ongoing phase III clinical trial in subjects with acute coronary syndrome. The understanding of mechanisms involved in HDL-based synthetic nanotherapeutics is critical to their design, therapeutic potential and effectiveness. In this review, we provide a current update on HDL-ApoA-I mimetic nanotherapeutics, highlighting the scope of treating vascular diseases by targeting monocytes and macrophages.